Mediação e competência em informação: percepção da Comissão de Educação de Usuários do Sistema de Bibliotecas da UFC - Almeida, Larisse Macêdo de (2019)
In the university environment, the library has an important role in the training of students as critical individuals, autonomous and with skills focused on access and appropriation of information. In this context, the mediation actions of the librarian should enable their interference in the information acquisition process aiming at the appropriation of the information to enable the construction of the user's knowledge. Thus, our objective is to analyze the perception, mediation and information competence, of the librarians in the process of construction of scientific knowledge in the university environment. This is a qualitative research, using the exploratory method. The data collected from questionnaires and interviews conducted with librarians who work at the User Education Committee of the library system of the Federal University of Ceará were analyzed by the technique of content analysis from the establishment of categories. Thus, the distinction between the concept of ability and competence is not clear and definite among librarians, even though they are put into practice on a daily basis, which does not allow them to associate the specific competence or ability to a particular activity. The professionals understand the essence of the concepts of mediation and information competence, but do not explain the intertwining of the themes. Nevertheless, the Commission is constantly seeking to align its planning with the needs of its users. Therefore, we conclude that the development of the Commission's activities has contributed to the consolidation of the research culture in the academic environment.